Emirates Mars Ultraviolet Spectrometer's (EMUS) Observation of Argon in the Martian Thermosphere. Issue 17 (9th September 2022) - Lootah, Fatma Hussain; Deighan, Justin; Fillingim, Matthew; Jain, Sonal; Evans, J. Scott; Al Matroushi, Hessa; Chaffin, Michael; Holsclaw, Gregory; Lillis, Robert; Al Mazmi, Hour; Correira, John; England, Scott
Abstract: The Emirates Mars Ultraviolet Spectrometer (EMUS) is a far ultraviolet spectrometer on‐board the Emirates Mars Mission's (EMM) which arrived at Mars on 9 February 2021. EMUS is designed to observe key neutral species in the Martian thermosphere (100–200 km) and exosphere (≥200 km). EMUS has observed two neutral argon (Ar) emission lines, Ar I 104.8 nm and Ar I 106.6 nm, in the thermosphere. Our interest in these emissions stem from argon's non‐reactiveness, making it a tracer for transport between the upper and lower atmosphere. We report average argon disk brightness measured by EMUS and compare them to measurements from Earth orbiting observatories. For the first time, this work investigates the variability of Ar I 106.6 nm brightness due to emission angles, solar zenith angles, solar longitudes, local times and latitudes. To contrast the behavior of inert argon we compare these results with the photochemically reactive oxygen 135.6 nm. Plain Language Summary: The Emirates Mars Ultraviolet Spectrometer (EMUS), on board of the Emirates Mars Mission, measures airglow from the upper atmosphere of Mars. Here we report on the first disk images of argon gas at Mars and compare them to past observations. We also compare the brightness of the argon to a well‐studied oxygen airglow feature. The optical depth of the argon airglow and how it is excited are discussed. Key Points: Emirates Mars Ultraviolet Spectrometer's (EMUS) provides first disk resolved images of argon in the thermosphere of Mars EMUS average disk brightness of argon I 104.8 nm and argon I 106.6 nm align with previous measurements reported in literature Argon I 106.6 nm is found to be optically thick and stimulated by fluorescent scattering as well as electron impact